The “war on fake news” and the emergence of truth as a public interest in Malaysia, Singapore and Thailand - Schuldt, Lasse (Đại học Quốc Gia Hà Nội, 2020)
This paper argues that truth is emerging as a legal interest in the public discourses of Malaysia, Singapore and Thailand. Though the criminal and media laws of several Southeast Asian countries have long addressed the dissemination of falsehoods, recent moves to ban “fake news” brought the issue to general attention. The professed function of the new legislation is to protect specified interests such as national security, public order and the integrity of democratic institutions. This paper inquires whether the protection of the truth is becoming increasingly disconnected from explicitly enumerated interests. For this purpose, the paper addresses how public interests are created and shaped, drawing mainly on communication and discourse theories. Constitutional texts, statutory and case law, official statements and media reporting are the material used to map the discourse. The paper describes a discursive process that is expected to result in new legal categories and enhanced powers of governments to restrict free speech.